Study of The Reactivity of Aromatic Nitrones Towards Acrylonitrile in Microemulsion: A Green Chemistry - Hamza, Kahina; Touati, Abdelkader; Ait Yahia, Ahmed; Baltas, Michel; Moulay, Saad (Asian Journal of Chemistry, 2010)
Cycloaddition reaction of a series of synthesized aromatic nitrones with acrylonitrile (ACN) was studied in toluene and in microemulsions made of water/ACN/(sodium dodecylsulfate/n-butanol = ½). The phase diagram of the latter system was worked out and revealed a wide domain of microemulsions, particularly in the vicinity of the water-borne region. Of these microemulsions, the oil-rich ones (W/O) gave the best results in the cycloaddition reaction. In the conventional medium (toluene), the reaction afforded mixtures of four diastereoisomers of isoxazolidines in moderate overall yields (ca. 30-70 %). However, the reactions in microemulsions were featured with relatively milder conditions (lower temperatures and shorter reaction times) and better yields, 60-80 % after 6 h at 25 ºC. Enhancement of the yields (80-100 %) was effected under the same reaction conditions, employing metal triflates Lewis acid catalysts in the microemulsion systems. A linear relationship between the temperature and the reaction time was found; a 25 ºC rise in temperature led to a reaction time drop of about 90 % to achieve nearly the same yield.